Candida bombicola as a platform organism for the production of tailor‐made biomolecules. Issue 9 (1st May 2013) - Roelants, Sophie L.K.W.; Saerens, Karen M.J.; Derycke, Thibaut; Li, Bing; Lin, Yao‐Cheng; Van de Peer, Yves; De Maeseneire, Sofie L.; Van Bogaert, Inge N.A.; Soetaert, Wim
Abstract The yeast Candida bombicola is capable of producing high amounts (400 g/L) of the biosurfactant sophorolipids. The genetic makeup of this industrially important yeast has recently been uncovered and molecular manipulation techniques have been developed. Hence, all tools for the development of new bioprocesses with C. bombicola are now available. As a proof of concept, the production of two totally different molecules was aimed for: the bioplastic polyhydroxyalkanoate (PHA) and a new‐to‐nature cellobioselipid‐biosurfactant. Integration of the new functionalities at genomic loci necessary for sophorolipid production safeguards the new biomolecules from sophorolipid contamination, while taking advantage of the regulation of the sophorolipid gene cluster. A maximum yield of 2.0% wt/dwt PHA was obtained; furthermore, this is the first time cellobioselipid synthesis by a non‐natural producer is reported. We here provided proof of concept that C. bombicola can be transformed into a platform organism for the production of tailor‐made biomolecules. Biotechnol. Bioeng. 2013; 110:2494–2503. © 2013 Wiley Periodicals, Inc.